Role of the Synthetic B1 Vitamin Sulbutiamine on Health - Bernardo Starling-Soares; Pedro Carrera-Bastos; Lucien Bettendorff (Journal of Nutrition and Metabolism)
Sulbutiamine is a thiamine derivative developed in Japan in the mid-60’s as a beriberi treatment drug. Since then, different potential applications have been described. For instance, there is some evidence that sulbutiamine can have anti-fatigue, nootropic, and antioxidant effects, which led to its use as a sport supplement (although some authors argue it is actually a masking doping strategy). Moreover, this molecule has been proposed as a possible treatment for some microsporidial infections and even for certain types of cancer. Despite these potential effects, sulbutiamine is still a relatively unknown molecule, which justifies the present review, where we discuss its history and the existing literature on its health applications. We conclude that there is a great potential for sulbutiamine use, well beyond its first described function (to increase thiamine tissue concentration). Indeed, new mechanisms of action have been found, mainly associated with its derivatives. Nevertheless, and although the research on sulbutiamine started 50 years ago, only a limited number of studies were conducted during this time frame. As so, methodological concerns need to be addressed and new studies are necessary, especially randomized controlled trials. Only then will the full potential of this versatile molecule be identified.